Optimal Hydro-Wind Power Generation for Day-Ahead Pool Market - Silva, António José Cerejo da (2019)
Wind power production is uncertain. The imbalance between power committed and delivered on pool markets produces increased costs on the system, which must be paid by defaulting producers, decreasing their revenues. In order to invert this situation wind producers may submit their bids join with hydro resources, due to their availability. This paper proposes an optimization technique regarding the maximum benefit for both producers, taking into account the wind unpredictability. A cascaded hydro system is considered.